ANALISIS MANAJEMEN PERENCANAAN TATA KELOLA SUKU CADANG KERETA LISTRIK CBTC - Achmad Handryanto; Adi Budipriyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
One of the solutions to Jakarta's transportation issues is the development ofrail-based transportation. Rail transportation has become a solution for masstransport.. Since urban trains are a public welfare facility, governance ofspare parts availability has an important role in maintaining the reliability of this mode of transportation. This study aims to determine the proper and goodclassification of electric train spare parts (Type J) in relation to determiningmanagement decisions for electric train spare parts (Type J). In particular theelectric train (Type J) is the first technology in Indonesia that uses theCommunication Based Train Control (CBTC) system. This study uses a semistructured interview method to obtain data on the classification of electrictrain spare parts as primary data. Railway Maintenance Division is therepresentative for operation, technical, supply point of view in managing theavailability of electric train spare parts. Referring to the predeterminedcriteria and sub-criteria, namely the Operational, Technical, and Supplycriteria, then the primary data obtained will be processed by the AHP methodthrough calculations using excel software and expert choice. Based on theresults of the combined calculation of the third level towards the purpose ofthis study, namely the criticality of electric train spare parts, experts considerthat for the criticality of electric train spare parts, it is necessary to managethe supply of electric train spare parts with priority on providing spare parts.From the results of the evaluation calculations, it shows that the expert choicesoftware can be used as a tool in calculating the AHP multi-criteria formanaging the supply of spare parts for electric trains. Then, based on theresults of the evaluation, the criteria and sub-criteria used in this study can beused as a reference for the classification analysis of the management of thesupply of electric train spare parts. The result of this research is the first stepfor further research on the management of spare parts inventory in the railwayindustry..